Correlation of High-Molecular-Weight Adiponectin and Leptin Concentrations with Anthropometric Parameters and Insulin Sensitivity in Newborns - Jia Zheng; Xinhua Xiao; Qian Zhang; Lili Mao; Ming Li; Miao Yu; Jianping Xu; Ying Wang (International Journal of Endocrinology)
Objective. High-molecular-weight adiponectin (HMW-adiponectin) and leptin are two important adipokines. The aim of this study was to examine the association between the two adipokines and anthropometric measurements of neonates at birth. Furthermore, we would like to explore whether HMW-adiponectin and leptin correlate with insulin sensitivity in neonates. Methods. Venous cord blood samples were obtained from 266 full-term healthy neonates consecutively born at Peking Union Medical College Hospital. HMW-adiponectin, leptin, blood glucose, and insulin concentrations were measured. Results. HMW-adiponectin and leptin were significantly higher in females compared with males (P=0.031 and P=0.000, resp.). Univariate correlation analysis showed that leptin concentrations in cord blood were positively associated with gestational age, birth weight, body length, ponderal index, placenta weight, insulin, and insulin sensitivity (all P<0.001). However, there was no correlation between cord blood HMW-adiponectin levels and foetal anthropometric measurements or foetal insulin sensitivity indicators (all P>0.05). Multivariate linear regression analysis indicated that leptin (B=-0.126, P=0.045) in cord blood was independently associated with insulin sensitivity. Conclusions. Leptin concentrations, but not HMW-adiponectin, were positively associated with foetal anthropometric measurements. Leptin concentrations are significantly associated with foetal insulin sensitivity, and there were no significant correlations between HMW-adiponectin levels and foetal insulin sensitivity.